Process optimisation for production and recovery of succinic acid using xylose-rich hydrolysates by Actinobacillus succinogenes - Jokodola, Esther Oreoluwa; Narisetty, Vivek; Castro, Eulogio; Durgapal, Sumit; Coulon, Frederic; Sindhu, Raveendran; Binod, Parameswaran; Banu, J. Rajesh; Kumar, Gopalakrishnan; Kumar, Vinod (Elsevier, 2021)
Succinic acid (SA) is a top platform chemical obtainable from biomass. The current study evaluated the potential of Actinobacillus succinogenes for SA production using xylose-rich hemicellulosic fractions of two important lignocellulosic feedstocks, olive pits (OP) and sugarcane bagasse (SCB) and the results were compared with pure xylose. Initial experiments were conducted in shake flask followed by batch and fed-batch cultivation in bioreactor. Further separation of SA from the fermented broth was carried out by adapting direct crystallisation method. During fed-batch culture, maximum SA titers of 36.7, 33.6, and 28.7 g/L was achieved on pure xylose, OP and SCB hydrolysates, respectively, with same conversion yield of 0.27 g/g. The recovery yield of SA accumulated on pure xylose, OP and SCB hydrolysates was 79.1, 76.5, and 75.2%, respectively. The results obtained are of substantial value and pave the way for development of sustainable SA biomanufacturing in an integrated biorefinery.
Keywords: Succinic acid; Actinobacillus succinogenes; Olive pits; Sugarcane bagasse; Pure xylose; Downstream processing